The Cosmic Significance of Directed Panspermia: Should Humanity Spread Life to Other Solar Systems? - Sivula Oskari (Cambridge University Press, 2025)
The possibility of seeding other planets with life poses a tricky dilemma. On the one hand, directed panspermia might be extremely good, while, on the other, it might be extremely bad depending on what factors are taken into consideration. Therefore, we need to understand better what is ethically at stake with planetary seeding. I map out possible conditions under which humanity should spread life to other solar systems. I identify two key variables that affect the desirability of propagating life throughout the galaxy. The first is axiological and depends on which value theory in environmental ethics is correct. The second is empirical and depends on whether life is common or not in our region of the universe. I also consider two ethical objections to an interplanetary life-seeding mission: the risk of interfering with indigenous life and the risk of increasing suffering in our galaxy.